2021
DOI: 10.3390/app12010036
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Recycled Aggregates, Washing Water and Cement Sludge Recovered from Returned Concrete

Abstract: In this paper, a new innovative technology for the treatment of returned concrete is proposed. This method is based on the application of physical–mechanical processes that allow to obtain new quality products: recycled aggregates, microfiltered water and cement sludge. Specifically, by means of a mechanical system equipped with buffer and Archimedes screws, fine (d < 5 mm) and coarse (d > 5 mm) aggregates are obtained. The water coming from the washing process is sent to a microfiltration process, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Regarding RCZ0, reported similar values in a study that investigated the mechanical performance of recycled aggregates derived from EM. Other studies have also reported the density for recycled aggregates obtained from ready mixed concrete waste within the range 1.65-2.72% [11,16,20,26]. It can also be mentioned that Norwegian rocks typically have a density within the range of 2.65-3.10 g/mL [16].…”
Section: Physical Propertiesmentioning
confidence: 97%
“…Regarding RCZ0, reported similar values in a study that investigated the mechanical performance of recycled aggregates derived from EM. Other studies have also reported the density for recycled aggregates obtained from ready mixed concrete waste within the range 1.65-2.72% [11,16,20,26]. It can also be mentioned that Norwegian rocks typically have a density within the range of 2.65-3.10 g/mL [16].…”
Section: Physical Propertiesmentioning
confidence: 97%
“…The circular economy, as an idea on the one hand, and as real action on the other hand, supports the construction industry by reducing its negative impact on the environment. Nowadays, mainly practical examples relating to concrete [35] and asphalt [36] technologies dominate the literature. However, this concept applies to every material and can be viewed from different angles represented by the various players involved in the Each working package related to the implementation of a new production effect is characterized by standard material usage.…”
Section: From Linear To Circular Economy In the Construction Sectormentioning
confidence: 99%